Energy efficient high performance processors : recent approaches for designing green high performance computing /: recent approaches for designing green high performance computing. (2018) - Haj-Yahya, Jawad; Mendelson, Avi; Ben-Asher, Yosi; Caṭṭopādhyāẏa, Anupama, 1956-
No abstract available